Using epigenomic studies in monozygotic twins to improve our understanding of cancer. (June 2014) - Roos, Leonie; D Spector, Timothy; G Bell, Christopher
Cancer is a set of diseases that exhibit not only genetic mutations but also a profoundly distorted epigenetic landscape. Over the last two decades, great advances have been made in identifying these alterations and their importance in the initiation and progression of cancer. Epigenetic changes can be seen from the very early stages in tumorigenesis and dysregulation of the epigenome has an increasingly acknowledged pathogenic role. Epigenomic twin studies have great potential to contribute to our understanding of complex diseases, such as cancer. This is because the use of monozygotic twins discordant for cancer enables epigenetic variation analysis without the confounding influence of the constitutive genetic background, age or cohort effects. It therefore allows the identification of susceptibility loci that may be sensitive to modification by the environment. These studies into cancer etiology will potentially lead to robust epigenetic markers for the detection and risk assessment of cancer.